resolva utilizando o método de adição 2x+y=-3 -x-y=1

Resposta :

[tex] > resolucao \\ \\ \geqslant sistema \: de \: equacao \\ \\ 2x + y = - 3 \\ - x - y = 1 \\ \\ x = - 2 \\ \\ y = - 3 - 2x \\ y = - 3 - ( - 4) \\ y = - 3 + 4 \\ y = 1 \\ \\ \\ s \: > \: \: ( \: \: x = - 2 \: \: e \: \: y = 1 \: \: ) \\ \\ \geqslant \leqslant \geqslant \leqslant \geqslant \geqslant \geqslant \geqslant \geqslant \geqslant [/tex]

Ver imagem EWERTON197775P7GWLB

Resposta:

S ={-2, 1}

1}

Explicação passo-a-passo:

2x+y = -3

-x-y=1

_______

x=2

-2-y=-1

-y=-1+2

-y=1 ×(-1)

y=1